Acute kidney injury: Clinical and epidemiological features and kidney function at discharge in a hospital in Peru - Palacios-Diaz, Rodolfo (2020)
Objetive: To describe the characteristics of Acute Kidney Injury (AKI) in hospitalized patients in a tertiary-level hospital from January to April of 2016. Material and methods: Retrospective descriptive study that included patients admitted to medical ward and Intensive Care Unit. AKI diagnosis and severity stage were established according to Kidney Disease: Improving Global Outcomes criteria. Kidney function at discharge was evaluated by estimating the glomerular filtration rate (GFR). Results: Overall frequency of AKI was 64.83%. In the medical ward, frequency was 57.06% and in ICU, 88.14%. Overall mortality was 27.45%. The proportion of patients with AKI who had anemia, diabetes and chronic kidney disease was 84.97%, 20.92% and 19.61%, respectively. According to severity stage, the overall frequency was stage 3: 46.41%, stage 1: 30.07% and stage 2: 23.53%. The most frequent categories of probable etiology were intrinsic (41.83%), prerenal (27.45%) and multifactorial (15.03%). The GFR median at discharge in ICU was 114.40 ml/min/1.73 m2, whereas in medical ward, 84.89 ml/min/1.73 m2. According to the severity stage, the lowest GFR median at discharge occurred in patients with stage 3 and, according to probable etiology, those who developed intrinsic and multifactorial AKI had lower kidney function at discharge. Conclusions: AKI is a frequent disorder in hospitalized patients. The GFR at discharge was significantly higher in patients who were in ICU than in medical ward.